PUBLIC-PRIVATE PARTNERSHIP IN THE MODERN ECONOMY: FOREIGN EXPERIENCE AND RUSSIAN PRACTICE - Tatiana V. Yurieva (Статистика и экономика, 2016)
The mechanism of interaction between the public and private partners at realization of projects in the form of public-private partnership is given. Foreign experience is analysed; the key prerequisites of the establishment and development of public-private partnerships in modern Russian economy are identified.